TRPM2 channel activation following in vitro ischemia contributes to male hippocampal cell death - Verma, S (2012)
Hippocampal CA1 neurons are particularly sensitive to ischemic damage, such as experienced following cardiac arrest and cardiopulmonary resuscitation. In recent years transient receptor potential M2 (TRPM2) channels have been identified as mediators of ischemic damage. We previously demonstrated that neuroprotective strategies targeting TRPM2 channels preferentially protect male cortical neurons from ischemic injury both in vitro and in vivo. It is important to determine the role of TRPM2 in ischemic injury of hippocampal neurons as this population of neurons are particularly sensitive to ischemic injury and are therapeutic targets. Here we report significantly decreased neuronal cell death following in vitro ischemia preferentially in male hippocampal neurons using TRPM2 inhibitors or knockdown of TRPM2 expression. Electrophysiological characterization of sex-stratified cultures shows similar levels of functional TRPM2 channel expression in male and female hippocampal neurons under basal conditions. In contrast, recordings made during reperfusion following in vitro ischemia revealed that TRPM2 channels are activated only in male neurons, resulting in rapid and complete depolarization. These findings provide strong evidence for TRPM2 as a target for protection against cerebral ischemia in male brain and helps define a molecular cell death pathway that is differentially engaged in male and female neurons.